The gender puzzles. (23rd April 2020) - Fileva, Iskra
Abstract: What is gender and how do we know what our gender is? These are the questions I propose to answer here. I review and reject several hypotheses: gender as sex or—a more careful version of the view—as subjective experiences that arise from sexual characteristics; gender as brain configuration; and gender as a historical kind. I express sympathy with an existentialist conception of gender but argue that such a conception, even according to its proponents, cannot help solve the problems of what gender is and how we know what our gender is. I then advance a new view.